Modes of spousal interaction and the labor market environment - Daniela Del Boca; Christopher J. Flinn (Institute for the Study of Labor (IZA), 2006)
We formulate a model of household behavior in which cooperation is costly and in which these costs vary across households. Some households rationally decide to behave noncooperatively, which in our context is an efficient outcome. An intriguing feature of the model is that, while the welfare of the spouses is continuous in the state variables, labor supply decisions are not. Small changes in state variables may result in large changes in labor supplies when the household switches its mode of behavior. We estimate the model using a nationally representative sample of Italian households and find that the costly cooperation model significantly outperforms a noncooperative model. This suggests the possibility of attaining large gains in aggregate labor supply by adopting policies which promote cooperative household behavior.
Keywords: C79; D19; J22; 330; household time allocation; Nash bargaining; Nash equilibrium; maximum likelihood